The Paradigm Shift in Web Application Data Management: An Analysis of React Query and Modern Data Handling Approaches - Tashi Garg (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the evolutionary transformation of data management within web applications, focusing specifically on React Query and similar modern technologies redefining how developers approach state management, data fetching, and synchronization. The historical context reveals a progression from direct DOM manipulation and AJAX calls toward more sophisticated paradigms, with Redux representing a significant but ultimately limiting milestone due to its verbose implementation requirements. Modern declarative data management systems fundamentally alter both development patterns and user experiences by conceptualizing server data as a continuously synchronized resource rather than a discrete state to be manually managed. The technical foundations of these systems—query-based data management, automatic cache management, and optimistic updates—integrate seamlessly with contemporary web ecosystems, including server components, GraphQL, and edge computing architectures. These integrations enable transformative user experience patterns such as real-time synchronization, optimistic interfaces, and offline-first capabilities. Case studies across e-commerce platforms, analytics dashboards, and collaborative editing systems demonstrate tangible benefits: reduced development complexity, enhanced performance, improved data reliability, and significantly better user experiences. This shift represents more than incremental improvement—it fundamentally redefines the relationship between applications and their data sources, enabling experiences that feel remarkably responsive and coherent while simultaneously reducing implementation complexity and technical debt.